Diabetes insipidus and Guillain-Barré-like syndrome following CAR-T cell therapy: a case report - Christian Koch; Patrick Roth; Juliane Fleischer; Todor Popov; Karl Frontzek; Bettina Schreiner; Markus G. Manz; Simone Unseld; Antonia M. S. Müller; Norman F. Russkamp (Journal for ImmunoTherapy of Cancer)
Background Immune effector cell-associated neurotoxicity syndrome (ICANS) is a common adverse event of CD19-directed chimeric antigen receptor (CAR) T cell therapy. Other neurological adverse events, however, have not methodically been described and studied. Furthermore, safety data on CAR-T cell therapy in patients with central nervous system (CNS) lymphoma remain limited.Main body We here report occurrence of a Guillain-Barré-like syndrome (GBS) and central diabetes insipidus (cDI) following tisagenlecleucel therapy for relapsed high-grade lymphoma with CNS involvement. Both complications were refractory to standard treatment of ICANS. Weakness of respiratory muscles required mechanical ventilation and tracheostomy while cDI was treated with desmopressin substitution for several weeks. Muscle-nerve biopsy and nerve conduction studies confirmed an axonal pattern of nerve damage. T cell-rich infiltrates and detection of the CAR transgene in muscle-nerve sections imply a direct or indirect role of CAR-T cell-mediated inflammation. In line with current treatment guidelines for GBS, intravenous immunoglobulin was administered and gradual but incomplete recovery was observed over the course of several months.Conclusions This case report highlights the risk of rare but severe neurological adverse events, such as acute GBS or cDI, in patients treated with CAR-T cells. It further underlines the importance of appropriate patient surveillance and systematic reporting of rare complications to eventually improve treatment.